Laparoscopic approach to a planned two‐stage hepatectomy for bilobar colorectal liver metastases. Issue 10 (2nd July 2014) - Kilburn, Daniel James; Chiow, Adrian Kah Heng; Lewin, Joel; Kienzle, Nicholas; Cavallucci, David Joseph; Bryant, Richard; O'Rourke, Nicholas
Abstract: Background: This report describes the technical aspects and outcomes of a laparoscopic approach in planned two‐stage liver resections for patients with bilobar colorectal cancer (CRC) liver‐only metastases. Methods: This is a retrospective review of our database examining consecutive patients who underwent an initial first‐stage laparoscopic liver resection for CRC metastases, with a planned second‐stage resection from 2007 to 2013. Results: Seven patients underwent an initial laparoscopic first stage with concurrent right portal vein ligation (RPVL) in two patients. Median operating time was 100 (60–170) min with a median blood loss of 100 (50–400) mL. Median length of stay was 3 (2–5) days. The remaining five patients required post‐operative right portal vein embolization (RPVE). All patients had significant hypertrophy of the future liver remnant (FLR) (future liver remnant volume (FLRV) >25%) and six patients subsequently had a successful open right hepatectomy with one attempted laparoscopically converted to open. Two patients had prolonged bile leaks after the second procedure. Three patients remained disease free, with median follow‐up of 34 (13–80) months. One patient had disease progression following RPVE precluding performance of second stage. Conclusion: Laparoscopic first‐stage resection of tumours in the left liver can be safely combined with RPVL/RPVE to achieve adequate hypertrophy of the FLR, allowing subsequent right hepatectomy.